Urban Projects and Religious Architecture in Post-War Cagliari: the Sant'Elia Village and its Church (1951-1956) - Stefano Mais (Histories of Postwar Architecture)
The first residential area planned and built in Cagliari after the Second World War was in Sant'Elia (1951-1956), selected after debateable political choices as an area of refuge for the poorer classes of the city’s population left homeless after the war. The neighbourhood is in the peripheral area known as Lazzaretto, where many displaced people had already found refuge during the war. Without basic services, the neighbourhood initially accommodated around 2,400 people. The physical and social centre of the Sant'Elia community was the parish church of the same name, one of the few services in the neighbourhood. The project started to be developed in 1956 by the architect Salvatore Rattu, responsible for the main local architectural projects before and after the Second World War. He acted on the suggestions put forward by Archbishop Paolo Botto, who was heavily committed to pastoral work involving the peripheral areas of the city. Despite its basic conformation, the church reflects the developing technical trends of national religious architecture and would become fundamental in the urban and social characterization of the neighbourhood.